2020
DOI: 10.1093/bib/bbaa001
|View full text |Cite
|
Sign up to set email alerts
|

The bioinformatics toolbox for circRNA discovery and analysis

Abstract: Circular RNAs (circRNAs) are a unique class of RNA molecule identified more than 40 years ago which are produced by a covalent linkage via back-splicing of linear RNA. Recent advances in sequencing technologies and bioinformatics tools have led directly to an ever-expanding field of types and biological functions of circRNAs. In parallel with technological developments, practical applications of circRNAs have arisen including their utilization as biomarkers of human disease. Currently, circRNA-associated bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
175
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(175 citation statements)
references
References 173 publications
0
175
0
Order By: Relevance
“…Studies of circRNAs rapidly increased in pace with the development of bioinformatics approaches that identify the sequences spanning circRNA back-splice junctions from total RNA-seq data. To date, several methods for circRNA identification have been developed 2 , but none clearly outperforms the others since they provide either highly sensitive or highly precise predictions 36 . CircRNA detection algorithms employ filtering procedures 36 that remove false-positive guesses (FPs) to improve precision, but that may also reject true circRNAs, thus increasing the number of false-negative predictions (FNs).…”
Section: Mainmentioning
confidence: 99%
“…Studies of circRNAs rapidly increased in pace with the development of bioinformatics approaches that identify the sequences spanning circRNA back-splice junctions from total RNA-seq data. To date, several methods for circRNA identification have been developed 2 , but none clearly outperforms the others since they provide either highly sensitive or highly precise predictions 36 . CircRNA detection algorithms employ filtering procedures 36 that remove false-positive guesses (FPs) to improve precision, but that may also reject true circRNAs, thus increasing the number of false-negative predictions (FNs).…”
Section: Mainmentioning
confidence: 99%
“…CircRNAs were first discovered in the 1970s [ 8 , 9 ] and were initially thought to be a non-functional by-product of aberrant splicing in cells [ 10 ]. However, recent advances in sequencing technologies have revealed that large numbers of circRNAs are broadly expressed in a wide range of mammalian tissue [ 11 ]. Over 30,000 circRNAs have already been found in human tissues [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the identification based on the back-splice junction, either segmented reads or a pseudo-reference can be used. The first approach is based on splitting the sequencing reads, whereas the latter is based on a pre-defined back-splice junction and its flanking sequences in a circRNA; next, the sequencing read is directly mapped against this pseudo-reference for identification of a back-splice site [ 106 ].…”
Section: Bioinformatic Toolsmentioning
confidence: 99%
“…This can be achieved via treatment of total RNA with RNase R, an exoribonuclease which degrades linear RNA molecules, poly(A) depletion, rRNA depletion, or combination of the aforementioned strategies. circRNA sequencing reads can be either single-end or paired-end [ 106 ].…”
Section: Bioinformatic Toolsmentioning
confidence: 99%